2010
DOI: 10.1108/09604521011011630
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the assessment of tangible service quality through the creation of a cleanliness measurement scale

Abstract: PurposeThe purpose of this paper is two‐fold: to enhance the tangible quality construct by considering cleanliness as a customer service quality dimension; and to assess customers' opinions on cleanliness by gender and education.Design/methodology/approachThe population under study is the general adult population of a Southwestern US city. The subjects voluntarily participate through a link to an anonymous online survey provided on a university's daily electronic news medium. Reliability and factor analyses ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
119
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(136 citation statements)
references
References 39 publications
(80 reference statements)
13
119
1
3
Order By: Relevance
“…Studies on housing have shown that tenants collectively value security and clean surroundings (Alford, 1998). In the hospitality industry, the link between cleanliness and perceived safety of restaurants and other food outlets has been studied extensively (Barber and Scarcelli, 2010). The link between security and cleanliness has also been indirectly validated by research that shows that items to measure security and cleanliness load on the same factor and are highly correlated (Jang and Wu, 2006;Sangpikul, 2008).…”
Section: Hypothesesmentioning
confidence: 98%
“…Studies on housing have shown that tenants collectively value security and clean surroundings (Alford, 1998). In the hospitality industry, the link between cleanliness and perceived safety of restaurants and other food outlets has been studied extensively (Barber and Scarcelli, 2010). The link between security and cleanliness has also been indirectly validated by research that shows that items to measure security and cleanliness load on the same factor and are highly correlated (Jang and Wu, 2006;Sangpikul, 2008).…”
Section: Hypothesesmentioning
confidence: 98%
“…Barber and Scarcelli (2010) conclude that customers tend to select, stay, and return to a service depending on the perceived degree of cleanliness.…”
Section: T Fernandes and S Nevesmentioning
confidence: 99%
“…In most studiesmost studies, cleanliness quality is considered as an attribute of environmental quality or of tangible quality (Liu and Jang, 2009;Lee et al, 2012;Bujisic et al, 2014). Recently, however, some research everal reports have suggested that cleanliness should be treated as a separate dimension due to its significant importance and impact on customer perception (Barber and Scarcelli, 2010). The cleanliness of restaurants must be considered for the importance of personal hygiene and safety w; which can measure the influence on service quality and the perception of service quality (Barber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%